Assessment of toxic element content of some grape molasses produced by conventional and industrial techniques: insights into human safety. (2nd October 2021) - Helvacıoğlu, Sinem; Charehsaz, Mohammad; Erdem, Onur; Aydın, Ahmet
Abstract: The level of arsenic, lead, cadmium, and aluminum in molasses produced by traditional and industrial techniques were investigated. The metal-induced non-carcinogenic and carcinogenic risks were calculated. All samples had a target hazard quotient and index ≤1 indicating no undue non-carcinogenic risk from exposure to a single or multiple toxic elements. Three samples produced traditionally exceed threshold limit of acceptable cancer risk. This assessment and the observation of higher levels of toxic metals in traditionally produced molasses is a concerning point for public health and the national authority needs to increase its supervision on the traditional food production.